PERSONAL KNOWLEDGE MANAGEMENT AND EMPLOYEE PERFORMANCE NEXUS WITH THRIVING AT WORK AS A MEDIATING FACTOR IN A PUBLIC ORGANIZATION CONTEXT - Ononye, Uzoma Heman; Ikechukwu, Madumezia (Jurnal Manajemen dan Kewirausahaan, 2024)
This study examined the relationship between personal knowledge management and employee performance by accounting for the mediational effect of thriving at work. The study used a cross-sectional survey to obtain data from 204 academic staff randomly sampled from state-owned universities in Delta State, Nigeria. The partial least squares method was applied to treat and analyze the data collected with the help of SmartPLS 4 software. The analysis revealed that knowledge sharing, creation, and acquisition were positively and significantly related to employee performance. Furthermore, the mediation role of thriving was also confirmed. In conclusion, personal knowledge management activities comprising knowledge sharing, knowledge creation, and knowledge acquisition, directly and indirectly, affected employee performance through thriving at work. The study recommended that public managers should incentivize and support the personalization of knowledge management activities across organizational levels, as it benefited thriving at work and employee performance, especially its adaptive aspects. Furthermore, personal knowledge management and thriving at work were driven or guided by knowledge, making organizations need to curate interventions to improve knowledge.